The impact of pharmacists’ interventions within the closed loop immunosuppressant management process on kidney transplant recipients: a retrospective cohort study - Chen, Hongxia; Li, Chuan; Ou, Shengsong; Chen, Xiaoyu (Frontiers in Immunology, 2025)
IntroductionNowadays, kidney transplant recipients’ primary challenge is improving graft function. However, they are rarely provided effective long-term instructions on immunosuppressant use after transplant. This study aimed to describe the experiences of a pharmacist-led, closed-loop immunosuppressant service (PLIS) in the transplant center of a general hospital in China.MethodsA retrospective pre-and post‐intervention study was conducted in the transplantation department in a general hospital. Of the 347 patients receiving kidney transplants from August 2022 to August 2024 were enrolled. Eligible subjects were assigned into two groups (pre‐intervention group and post‐intervention group) according to the date (1 August 2023) when the pharmacist commenced participation in the post‐transplant management for kidney transplant recipients. The intra-patient variation in immunosuppressant trough concentrations (Cmin) before and after the intervention was defined as the primary outcome. The secondary outcome was to assess the impact on renal function.ResultsAmong 347 patients (August 2022–2024), those managed post-intervention (from August 2023) showed improved target trough concentration (Cmin) attainment versus pre-intervention: tacrolimus (TAC, 72.4% vs. 58.3%, P=0.012), cyclosporine (CsA, 63.7% vs. 46.5%, P=0.037), mycophenolate (MMF, 76.0% vs. 65.3%, P=0.025), and sirolimus (SRL, 80.2% vs. 51.9%, P=0.018). Compared to pre-intervention, the percentage coefficient of variation (%CV) decreased significantly for TAC (18.28% vs. 8.92%, P=0.031) and CsA (22.97% vs. 7.14%, P=0.004) post-intervention, while MMF maintained high variability (CV >30%). SRL variability declined at 6–12 months (17.02% vs. 26.05%, P=0.194). Renal function improved post-intervention, with reductions in serum creatinine, urea nitrogen, cystatin C, and microproteinuria (P<0.05).ConclusionPLIS enhanced immunosuppressant management precision and graft outcomes, demonstrating its utility in standardizing post-transplant care.